Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1101/2020.01.25.919688
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MRCA time and epidemic dynamics of the 2019 novel coronavirus

Abstract: 11The 2019 novel coronavirus (2019-nCoV) have emerged from Wuhan, China. Studying the 12 epidemic dynamics is crucial for further surveillance and control of the outbreak. We employed 13 a Bayesian framework to infer the time-calibrated phylogeny and the epidemic dynamics 14 represented by the effective reproductive number (Re) changing over time from 33 genomic 15 sequences available from GISAID. The time of the most recent common ancestor (MRCA) 16

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 15 publications
7
27
0
Order By: Relevance
“…1a). The excess of low frequency mutations is consistent with the recent origin of SARS-CoV-2 [19]. Both population reduction and positive selection can increase high frequency mutations [20, 21].…”
Section: Resultssupporting
confidence: 69%
“…1a). The excess of low frequency mutations is consistent with the recent origin of SARS-CoV-2 [19]. Both population reduction and positive selection can increase high frequency mutations [20, 21].…”
Section: Resultssupporting
confidence: 69%
“…For all periods the effective reproduction numbers decrease in time. As new data were reported daily, we followed with subsequent analysis in near-real time with three periods as shown in Table 2 In contrast, a simple linearization of Re in time (Figure 3) back-estimated the original basic reproduction number R0 at about 2.4 to 2.5, agreeing well with other values recently reported Liu et al, 2020;Majumder & Mandl, 2020;Zhang & Wang, 2020a, 2020bZhao et al, 2020a). The discrepancy between these two estimates can be attributed a potential loss of virulence of the virus but most likely due to extreme measures to contain virus spread in China.…”
Section: Resultssupporting
confidence: 80%
“…Using statistical approaches, namely exponential growth and maximum likelihood techniques, Liu and colleagues (Liu et al, 2020) estimated the value of the reproduction number ranging from 2.90 (95% CI 2.32e3.63) to 2.92 (95% CI 2.28e3.67). Zhang and Wang (Zhang & Wang, 2020), employing a Bayesian framework to infer time-calibrated phylogeny from 33 available genomic sequences, found that the time of the most recent common ancestor (MRCA) was December 17th , 2019 (95% highest posterior density interval from December 7th , 2019 to December 23rd , 2019) and that the value of the reproduction number oscillated between 1.1 and 1.6.…”
Section: Discussionmentioning
confidence: 99%